Choline‐mediated modulation of hippocampal sharp wave–ripple complexes in vitro. (19th March 2014) - Fischer, Viktoria; Both, Martin; Draguhn, Andreas; Egorov, Alexei V.
Abstract The cholinergic system is critically involved in the modulation of cognitive functions, including learning and memory. Acetylcholine acts through muscarinic (mAChRs) and nicotinic receptors (nAChRs), which are both abundantly expressed in the hippocampus. Previous evidence indicates that choline, the precursor and degradation product of Acetylcholine, can itself activate nAChRs and thereby affects intrinsic and synaptic neuronal functions. Here, we asked whether the cellular actions of choline directly affect hippocampal network activity. Using mouse hippocampal slices we found that choline efficiently suppresses spontaneously occurring sharp wave–ripple complexes (SPW‐R) and can induce gamma oscillations. In addition, choline reduces synaptic transmission between hippocampal subfields CA3 and CA1. Surprisingly, these effects are mediated by activation of both mAChRs and α7‐containing nAChRs. Most nicotinic effects became only apparent after local, fast application of choline, indicating rapid desensitization kinetics of nAChRs. Effects were still present following block of choline uptake and are, therefore, likely because of direct actions of choline at the respective receptors. Together, choline turns out to be a potent regulator of patterned network activity within the hippocampus. These actions may be of importance for understanding state transitions in normal and pathologically altered neuronal networks. <boxed-text content-type="graphic" id="jnc12693-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text> In this study we asked whether choline, the precursor and degradation product of acetylcholine, directly affects hippocampal network activity. Using mouse hippocampal slices we found that choline efficiently suppresses spontaneously occurring sharp wave–ripple complexes (SPW‐R). In addition, choline reduces synaptic transmission between hippocampal subfields. These effects are mediated by direct activation of muscarinic as well as nicotinic cholinergic pathways. Together, choline turns out to be a potent regulator of patterned activity within hippocampal networks.